Modified epoxy resin, waterborne graphene composite coating and preparation method and application thereof

By chemically modifying the epoxy resin, modifying the modified epoxy resin, and combining graphene powder to prepare an aqueous graphene composite coating, the problem of insufficient adhesion caused by agglomeration of graphene in aqueous media is solved, and the excellent adhesion and corrosion resistance of the coating are achieved.

CN119638955APending Publication Date: 2025-03-18CHONGQING GRAPHENE RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411950137.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The composite coating of aqueous graphene is prone to agglomeration in aqueous media, resulting in uneven dispersion and poor performance, especially insufficient adhesion, which makes it easy to fall off and peel off.

Method used

By reacting the epoxy resin with stearic acid to introduce the ester group for chemical modification, a modified epoxy resin was prepared, and an aqueous graphene composite coating was prepared based on the modified epoxy resin.

Benefits of technology

The adhesion of the aqueous graphene composite coating was significantly improved, and the adhesion reached level 1 through standard tests, and the impact strength reached 38cm, which improved the anticorrosion performance and service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214662550000071
    Figure BDA0005214662550000071
  • Figure BDA0005214662550000081
    Figure BDA0005214662550000081
Patent Text Reader

Abstract

The invention belongs to the technical field of surface treatment, and particularly relates to a modified epoxy resin and water-based graphene composite coating as well as a preparation method and application thereof. The modified epoxy resin is prepared by reacting epoxy resin with stearic acid and introducing ester groups to modify the epoxy resin. The water-based graphene composite coating prepared on the basis of the modified epoxy resin provided by the invention has excellent corrosion resistance and excellent adhesive force, the adhesive force can reach grade 1 through a standard 'ISO 2409' test, and the impact strength can reach 38cm through a standard 'GB / T 1732-2020' test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and specifically relates to a modified epoxy resin, water-based graphene composite coating, and a preparation method and application thereof. Background Art

[0002] Water-based graphene composite coatings are more environmentally friendly than oil-based coatings, and contain graphene (graphene has a large specific surface area and excellent barrier properties, which can form a tortuous path in the coating, delaying the contact between the corrosive medium and the substrate surface through the coating, thereby improving the corrosion resistance of the coating). This makes the coating have excellent anti-corrosion performance and is one of the most popular surface treatment coatings. Especially in metal surface treatment, water-based graphene composite coatings can slow down the corrosion rate of metals to a certain extent and extend their service life.

[0003] However, it is not easy to apply graphene to water-based coatings. In water-based coatings, graphene is prone to agglomeration and uneven dispersion, resulting in poor performance of water-based graphene composite coatings, especially adhesion. The reduction in adhesion will easily lead to shedding and peeling, which will directly affect the life of the coated products.

[0004] The prior art discloses that graphene is uniformly dispersed in epoxy resin to form a stable coating system, thereby improving adhesion. Therefore, it is potential to develop a water-based graphene composite coating based on epoxy resin. Summary of the invention

[0005] The invention prepares a modified epoxy resin by chemically modifying the epoxy resin by introducing an ester group into stearic acid. The water-based graphene composite coating prepared based on the modified epoxy resin has excellent adhesion, especially as a coating on a metal surface.

[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:

[0007] On one hand, the present invention provides a modified epoxy resin, which is prepared by introducing an ester group into the epoxy resin through the reaction of epoxy resin and stearic acid.

[0008] Preferably, the viscosity of the modified epoxy resin in the present invention at 25° C. is 1700 mPa·s-1850 mPa·s.

[0009] Another aspect of the present invention provides a method for preparing the modified epoxy resin of the present invention, which comprises: mixing epoxy resin, stearic acid, a catalyst and a solvent, and reacting at 100° C.-140° C. to prepare the modified epoxy resin.

[0010] Preferably, the preparation method satisfies one or more of the following conditions: (i) the catalyst is selected from one or more of triethylamine, hexadecyltrimethylammonium chloride or boron trifluoride; (ii) the solvent is selected from one or more of dimethylformamide, cyclohexanol, ethylene glycol monomethyl ether or cyclohexanone.

[0011] Preferably, in the above preparation method, the mass ratio of epoxy resin to stearic acid is 100:(3-7).

[0012] In another aspect, the present invention provides a water-based graphene composite coating, which comprises the modified epoxy resin of the present invention and graphene powder.

[0013] Preferably, the above-mentioned water-based graphene composite coating includes, by mass fraction, 30%-50% modified epoxy resin, 0.5%-3% graphene powder, 2%-3% pigment, 3%-5% filler, 0.1%-1% dispersant, 0.01%-0.1% defoamer, 0.1%-2% thickener, 0.1%-1% leveling agent and balance water.

[0014] Preferably, the above-mentioned water-based graphene composite coating satisfies one or more of the following conditions: (a) the pigment is selected from one or more of red iron oxide, yellow iron oxide, titanium dioxide or carbon black; (b) the filler is selected from one or more of mica powder, talc, kaolin, silica lime or barium sulfate; (c) the dispersant is selected from aqueous dispersant B6090 and / or aqueous dispersant CY108; (d) the defoamer is selected from one or more of polyether surfactants, polyethylene glycol fatty acid esters, stearic acid metal soaps or polyureas; (e) the thickener is selected from one or more of hydroxyethyl cellulose, bentonite, polyacrylate or acrylic acid; (f) the leveling agent is selected from polydimethylsiloxane and / or its modified substances.

[0015] More preferably, the water-based graphene composite coating comprises, by mass fraction, 40% modified epoxy resin, 2% graphene powder, 2.5% titanium dioxide, 4% mica powder, 0.5% aqueous dispersant B6090, 0.05% polyethylene glycol fatty acid ester, 1% bentonite, 0.5% polydimethylsiloxane and the remainder water.

[0016] Another aspect of the present invention provides an application of the water-based graphene composite coating of the present invention in metal surface treatment.

[0017] The beneficial effects of the present invention include: the water-based graphene composite coating prepared based on the modified epoxy resin provided by the present invention has excellent anti-corrosion performance and excellent adhesion. The adhesion can reach level 1 through the standard "ISO 2409" test, and the impact strength can reach 38cm through the standard "GB / T 1732-2020" test. DETAILED DESCRIPTION

[0018] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.

[0019] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.

[0020] The embodiment of the present invention provides a modified epoxy resin, which is prepared by introducing an ester group into the epoxy resin through a reaction between epoxy resin and stearic acid.

[0021] It should be noted that the present invention prepares a modified epoxy resin by chemically modifying the epoxy resin using stearic acid to introduce an ester group, and the modified epoxy resin is applied to the water-based graphene composite coating, which can significantly improve the adhesion compared with the unmodified epoxy resin.

[0022] In some specific examples, the viscosity of the modified epoxy resin in the present invention at 25° C. is 1700 mPa·s-1850 mPa·s, such as 1750 mPa·s, 1800 mPa·s or 1820 mPa·s.

[0023] The embodiment of the present invention further provides a method for preparing the modified epoxy resin of the present invention, which comprises: mixing epoxy resin, stearic acid, a catalyst and a solvent, and reacting at 100° C.-140° C. to prepare the modified epoxy resin.

[0024] It should be noted that the method of modifying epoxy resin by introducing ester groups by reacting epoxy resin with stearic acid is well known in the art. For example, a chemical modification method can be used, in which the epoxy resin, stearic acid, a catalyst and a solvent are mixed and reacted at 100°C-140°C. The temperature can be 110°C, 120°C or 130°C, etc. The method for detecting whether the reaction is complete can be through a viscosity test.

[0025] In some specific examples, the preparation method satisfies one or more of the following conditions: (i) the catalyst is selected from one or more of triethylamine, hexadecyltrimethylammonium chloride or boron trifluoride; (ii) the solvent is selected from one or more of dimethylformamide, cyclohexanol, ethylene glycol monomethyl ether or cyclohexanone.

[0026] It should be noted that the catalyst and solvent of the preparation method of the present invention can be selected from the above catalysts and solvents according to the situation. The catalyst can be preferably triethylamine, which has a better catalytic effect than other catalysts, and the solvent can be dimethylformamide.

[0027] In some specific examples, in the above preparation method, the mass ratio of epoxy resin to stearic acid is 100:(3-7), such as 100:4, 100:5 or 100:6, etc., preferably 100:5, and the water-based graphene composite coating prepared by the modified epoxy resin has better performance.

[0028] An embodiment of the present invention further provides a water-based graphene composite coating, which includes the modified epoxy resin and graphene powder in the present invention.

[0029] It should be noted that, as described above, the modified epoxy resin in the present invention can be combined with graphene powder to prepare a water-based graphene composite coating with good corrosion resistance and excellent adhesion.

[0030] In some specific examples, the water-based graphene composite coating includes, by mass fraction, 30%-50% modified epoxy resin, 0.5%-3% graphene powder, 2%-3% pigment, 3%-5% filler, 0.1%-1% dispersant, 0.01%-0.1% defoamer, 0.1%-2% thickener, 0.1%-1% leveling agent and balance water.

[0031] In some specific examples, the modified epoxy resin can be 30%-50%, such as 32%, 35%, 38%, 40%, 45% or 47%, etc.; the graphene powder can be 0.5%-3%, such as 1%, 1.5%, 2% or 2.5%, etc., the graphene powder can be 0.5%-3%, such as 1%, 2% or 2.5, etc., the pigment can be 2%-3%, such as 2.3%, 2.5% or 2.8%, etc., and the filler can be 3%-5%, such as 3.3%. , 3.5% or 4%, etc., the dispersant can be 0.1%-1%, such as 0.3%, 0.5% or 0.8%, etc., the defoamer can be 0.01%-0.1%, such as 0.03%, 0.05% or 0.08%, etc., the thickener can be 0.1%-2%, such as 0.3%, 1% or 1.5, etc., the leveling agent can be 0.1%-1%, such as 0.2%, 0.5% or 0.8%, etc.; it should also be understood that water can be preferably deionized water.

[0032] In some specific examples, the above-mentioned water-based graphene composite coating satisfies one or more of the following conditions: (a) the pigment is selected from one or more of red iron oxide, yellow iron oxide, titanium dioxide or carbon black; (b) the filler is selected from one or more of mica powder, talc, kaolin, silica lime or barium sulfate; (c) the dispersant is selected from aqueous dispersant B6090 and / or aqueous dispersant CY108; (d) the defoamer is selected from one or more of polyether surfactants, polyethylene glycol fatty acid esters, stearic acid metal soaps or polyureas; (e) the thickener is selected from one or more of hydroxyethyl cellulose, bentonite, polyacrylate or acrylic acid; (f) the leveling agent is selected from polydimethylsiloxane and / or its modified substances.

[0033] In some specific examples, the water-based graphene composite coating includes, by mass fraction, 40% modified epoxy resin, 2% graphene powder, 2.5 titanium dioxide, 4% mica powder, 0.5% aqueous dispersant B6090, 0.05% polyethylene glycol fatty acid ester, 1% bentonite, 0.5% polydimethylsiloxane and the remainder water.

[0034] It should be noted that the water-based graphene composite coating of the present invention can preferably be the above combination, and the water-based graphene composite coating prepared by the combination can have an adhesion of level 1 and an impact strength of 38 cm.

[0035] An embodiment of the present invention also provides an application of the water-based graphene composite coating of the present invention in metal surface treatment.

[0036] It should be noted that the water-based graphene composite coating in the present invention is suitable for metal surface treatment, and the metal may be steel (such as structural steel, carbon steel or alloy steel, etc.), aluminum or magnesium.

[0037] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.

[0038] 1. Preparation of modified epoxy resin

[0039] Example 1

[0040] 100 g of epoxy resin (Fengguang brand E-44 (6101) purchased from Shandong Pinshang New Materials Co., Ltd., the same below) was weighed and put into a three-necked flask, 80 g of dimethylformamide was added for dissolution, and then 3 g of stearic acid and 0.3 g of triethylamine were added and placed in the three-necked flask, the three-necked flask was placed on an electromagnetic heater for reaction, and magnetic stirring was performed at 130°C; the viscosity of the reactants was monitored during the reaction (tested by an NDJ-5S digital display viscometer, the same below), when the viscosity reached 733 mPa·s (reaction for 15 hours), 0.1 g of p-cresol was added to terminate the reaction, and heating was stopped at the same time; cooled to room temperature, the viscosity was tested to be 1572 mPa·s, and a modified epoxy resin was obtained.

[0041] Example 2

[0042] 100 g of epoxy resin was weighed and put into a three-necked flask, 80 g of dimethylformamide was added to dissolve it, and then 5 g of stearic acid and 0.3 g of triethylamine were added and placed in the three-necked flask, the three-necked flask was placed on electromagnetic heating for reaction, and magnetic stirring was performed at 130° C. During the reaction, the viscosity of the reactants was monitored. When the viscosity reached 754 mPa·s (reaction time 15 h), 0.1 g of p-cresol was added to terminate the reaction, and heating was stopped at the same time; it was cooled to room temperature, and the viscosity was tested to be 1791 mPa·s, thereby obtaining a modified epoxy resin.

[0043] Example 3

[0044] 100 g of epoxy resin was weighed and put into a three-necked flask, 80 g of dimethylformamide was added to dissolve it, and then 7 g of stearic acid and 0.3 g of triethylamine were added and placed in the three-necked flask, the three-necked flask was placed on electromagnetic heating for reaction, and magnetic stirring was performed at 130° C. During the reaction, the viscosity of the reactants was monitored. When the viscosity reached 790 mPa·s (reaction time 15 h), 0.1 g of p-cresol was added to terminate the reaction, and heating was stopped at the same time; it was cooled to room temperature, and the viscosity was tested to be 1803 mPa·s, thereby obtaining a modified epoxy resin.

[0045] Comparative Example 1

[0046] Weigh 100g of epoxy resin into a three-necked flask, add 80g of dimethylformamide to dissolve, then add 3g of oleic acid and 0.3g of triethylamine and place them in the three-necked flask, place the three-necked flask on electromagnetic heating for reaction, and perform magnetic stirring at 130°C; monitor the viscosity of the reactants during the reaction, when the viscosity reaches 721mPa·s (reaction 15h), add 0.1g of p-cresol to terminate the reaction, and stop heating at the same time; cool to room temperature, test the viscosity of 1672mPa·s, and obtain a modified epoxy resin.

[0047] 2. Preparation of water-based graphene composite coating

[0048] Example 4

[0049] The modified epoxy resin prepared in Example 2, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder) and additives (aqueous dispersant B6090 (purchased from Jining Tangyi Chemical Co., Ltd., the same below), polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) and deionized water were mixed in the amounts shown in Table 1 below, and stirred to prepare a water-based graphene composite coating.

[0050] Table 1 Amounts of different raw materials added in Example 4

[0051] Components Addition amount (g) Modified epoxy resin prepared in Example 2 300 Hexamethylenediamine 250 Graphene powder 5 Titanium dioxide 20 Mica powder 30 Water-based dispersant B6090 1 Polyethylene glycol fatty acid esters 0.1 Bentonite 1 Dimethicone 1 Deionized water Add to 1000

[0052] Example 5

[0053] The modified epoxy resin prepared in Example 2, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder) and additives (aqueous dispersant B6090, polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) and deionized water were mixed in the amounts shown in Table 2 below, and stirred to prepare a water-based graphene composite coating.

[0054] Table 2 Amounts of different raw materials added in Example 5

[0055] Components Addition amount (g) Modified epoxy resin prepared in Example 2 400 Hexamethylenediamine 300 Graphene powder 20 Titanium dioxide 25 Mica powder 40 Water-based dispersant B6090 5 Polyethylene glycol fatty acid esters 0.5 Bentonite 10 Dimethicone 5 Deionized water Add to 1000

[0056] Example 6

[0057] The modified epoxy resin prepared in Example 2, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder) and additives (aqueous dispersant B6090, polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) and deionized water were mixed in the amounts shown in Table 3 below, and stirred to prepare a water-based graphene composite coating.

[0058] Table 3 Amounts of different raw materials added in Example 6

[0059] Components Addition amount (g) Modified epoxy resin prepared in Example 2 500 Hexamethylenediamine 350 Graphene powder 30 Titanium dioxide 30 Mica powder 50 Water-based dispersant B6090 10 Polyethylene glycol fatty acid esters 1 Bentonite 20 Dimethicone 10 Deionized water Add to 1000

[0060] Example 7

[0061] The modified epoxy resin prepared in Example 1, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder) and additives (aqueous dispersant B6090, polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) and deionized water were mixed in the amounts shown in Table 3 below, and stirred to prepare a water-based graphene composite coating.

[0062] Table 4 Amounts of different raw materials added in Example 7

[0063] Components Addition amount (g) Modified epoxy resin prepared in Example 1 400 Hexamethylenediamine 300 Graphene powder 20 Titanium dioxide 25 Mica powder 40 Water-based dispersant B6090 5 Polyethylene glycol fatty acid esters 0.5 Bentonite 10 Dimethicone 5 Deionized water Add to 1000

[0064] Example 8

[0065] The modified epoxy resin, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder) and additives (aqueous dispersant B6090, polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) prepared in Example 1 and deionized water were mixed in the amounts shown in Table 5 below and stirred to prepare a water-based graphene composite coating.

[0066] Table 5 Amounts of different raw materials added in Example 8

[0067] Components Addition amount (g) Modified epoxy resin prepared in Example 3 400 Hexamethylenediamine 300 Graphene powder 20 Titanium dioxide 25 Mica powder 40 Water-based dispersant B6090 5 Polyethylene glycol fatty acid esters 0.5 Bentonite 10 Dimethicone 5 Deionized water Add to 1000

[0068] Comparative Example 2

[0069] The modified epoxy resin, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder) and additives (aqueous dispersant B6090, polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) prepared in Comparative Example 1 and deionized water were mixed in the amounts shown in Table 6 below and stirred to prepare a water-based graphene composite coating.

[0070] Table 6 Different raw material addition amounts in Comparative Example 2

[0071]

[0072]

[0073] Comparative Example 3

[0074] Epoxy resin, hexamethylenediamine, graphene powder, pigments and fillers (titanium dioxide and mica powder), additives (water-based dispersant B6090, polyethylene glycol fatty acid ester, bentonite and polydimethylsiloxane) and deionized water were mixed in the amounts shown in Table 7 below, and stirred to prepare a water-based graphene composite coating.

[0075] Table 6 Different raw material addition amounts in comparative example 3

[0076] Components Addition amount (g) Epoxy resin 400 Hexamethylenediamine 300 Graphene powder 20 Titanium dioxide 25 Mica powder 40 Water-based dispersant B6090 5 Polyethylene glycol fatty acid esters 0.5 Bentonite 10 Dimethicone 5 Deionized water Add to 1000

[0077] 3. Performance test of water-based graphene composite coating

[0078] The water-based graphene composite coatings prepared in the embodiment and the comparative example were uniformly coated on the Q345 steel parts, and the appearance of the coatings was observed. After the coatings were dry (3h), the adhesion was tested according to the standard "ISO 2409", the impact strength was tested according to the standard "GB / T 1732-2020", and the salt spray test was performed according to the standard "GB / T 10125-2021"; the test results are shown in Table 7 below.

[0079] Table 7 Properties of water-based graphene composite coatings prepared in Examples and Comparative Examples

[0080] performance Coating appearance Adhesion, Grade Impact strength, cm Salt spray test, h Example 4 Even and smooth Level 1 33 700h no change Example 5 Even and smooth Level 1 38 700h no change Example 6 Even and smooth Level 1 35 700h no change Example 7 Even and smooth Level 1 36 700h no change Example 8 Even and smooth Level 1 34 700h no change Comparative Example 2 Even and smooth 2 27 700h with bubbling Comparative Example 3 Even and smooth 3 26 700h no change

[0081] It can be seen from Table 7 above that the adhesion and impact strength of the water-based graphene composite coating prepared by modifying the epoxy resin using stearic acid are significantly better than those of the water-based graphene composite coating prepared by modifying the epoxy resin using oleic acid and the water-based graphene composite coating not prepared by modification; and the corrosion resistance of the water-based graphene composite coating prepared by modifying the epoxy resin using oleic acid is weaker than that of the water-based graphene composite coating prepared by modification; Among them, the water-based graphene composite coating prepared in Example 5 has the best adhesion, the adhesion can reach level 1, and the impact strength can reach 38cm.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.

Claims

1. A modified epoxy resin, characterized in that: The epoxy resin is prepared by introducing an ester group into the epoxy resin through the reaction of epoxy resin and stearic acid.

2. The modified epoxy resin according to claim 1, characterized in that Its viscosity at 25°C is 1700 mPa·s-1850 mPa·s.

3. The method for preparing the modified epoxy resin according to claim 1 or 2, characterized in that: include: The epoxy resin, stearic acid, a catalyst and a solvent are mixed and reacted at 100-140° C. to prepare the modified epoxy resin.

4. The preparation method according to claim 2, characterized in that: The preparation method meets one or more of the following conditions: (i) the catalyst is selected from one or more of triethylamine, hexadecyltrimethylammonium chloride or boron trifluoride; (ii) The solvent is selected from one or more of dimethylformamide, cyclohexanol, ethylene glycol monomethyl ether or cyclohexanone.

5. The modified epoxy resin according to claim 3 or 4, characterized in that The mass ratio of epoxy resin to stearic acid is 100:(3-7).

6. A water-based graphene composite coating, characterized in that: It comprises the modified epoxy resin according to claim 1 or 2 and graphene powder.

7. The water-based graphene composite coating according to claim 6, characterized in that: Calculated by mass fraction, it includes 30%-50% modified epoxy resin, 0.5%-3% graphene powder, 2%-3% pigment, 3%-5% filler, 0.1%-1% dispersant, 0.01%-0.1% defoamer, 0.1%-2% thickener, 0.1%-1% leveling agent and balance water.

8. The water-based graphene composite coating according to claim 7, characterized in that: It meets one or more of the following conditions: (a) the pigment is selected from one or more of red iron oxide, yellow iron oxide, titanium dioxide or carbon black; (b) filler selected from one or more of mica powder, talc, kaolin, silica lime or barium sulfate; (c) a dispersant selected from aqueous dispersant B6090 and / or aqueous dispersant CY108; (d) a defoamer selected from one or more of a polyether surfactant, a polyethylene glycol fatty acid ester, a stearic acid metal soap or a polyurea; (e) a thickener selected from one or more of hydroxyethyl cellulose, bentonite, polyacrylate or acrylic acid; (f) The leveling agent is selected from polydimethylsiloxane and / or its modified substances.

9. The water-based graphene composite coating according to claim 8, characterized in that: Calculated by mass fraction, it includes 40% modified epoxy resin, 2% graphene powder, 2.5% titanium dioxide, 4% mica powder, 0.5% aqueous dispersant B6090, 0.05% polyethylene glycol fatty acid ester, 1% bentonite, 0.5% polydimethylsiloxane and the balance water.

10. Use of the water-based graphene composite coating according to any one of claims 6 to 9 in metal surface treatment.